Thermoregulatory Responses in the Cold-Effect of an Extended Cold Weather Clothing System (ECWCS) - Gonzalez, Richard R.; Endrusick, Thomas L.; Santee, William L. (1989)
This report addresses the human thermoregulatory responses of wearing a new cold-weather system (ECWCS) at rest or during exercise. The ECWCS (insulation = 3.6 clo; weight = 10.1 kg) encompasses skin- tight polypropylene underwear, polyester/cotton fatigues; polyester-insulated liners, balaclava, vapor-barrier boots, and polytetrafluorethylene (PTFE)-lined outer garments. Six fit males each rested and did treadmill exercise while wearing different handwear with the ECWCS; the handwear included: a light duty glove heavy duty glove, or an Arctic mitten. A maximal 120 min cold challenge for each soldier was designated (based on physiological safety measures) as a maximal endurance time (ET,min). A multiple correlation analysis demonstrated that ET could be predicted adequately by finger temperature, absolute metabolism, rectal and 10- site skin temperatures. Effect of sweating during exercise reduced the effective thermal insulation of the ensemble thereby lowering the ET's for each handwear item. The Arctic mitten rendered the highest ETs during rest or exercise. The ECWCS should tender adequate endurance times in cold-dry ambients provided that ventilation and removal of extra layers is allowed as an easy option during heavy exercise so that thermal insulation is not excessively decreased by body moisture. Keywords: Cold stress, Extended cold weather clothing; Thermo- regulatory responses; Exercise; Endurance time; Handwear; Vasoconstrictor response.